Basic of cardiopulmonary physical therapy - Malik, Rajni (Panamá : Jaypee Brothers Medical, 2014)
La obra ofrece un panorama exhaustivo: desde los principios básicos hasta la cobertura profunda de las técnicas más recientes.
Section I. Introduction to cardiopulmonary system Section 2. Role of physioterapy in cardiopulmonary diseases Section 3. Respiratory system Section 4. Cardio vascular system
Keywords: Cardiopulmonar